2013
DOI: 10.1159/000356587
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors of Severe Acute Kidney Injury Induced by Cisplatin

Abstract: Objectives: We reported that the KDIGO (Kidney Disease: Improving Global Outcomes) criteria could stratify the risk of mortality in acute kidney injury (AKI) caused by cisplatin. The purpose of this study was to investigate risk factors of severe cisplatin-induced AKI (CIA). Methods: From January 2006 to December 2012, we identified Japanese cancer patients who were treated with cisplatin as a first-line chemotherapy at Nagoya University Hospital. Serum creatinine levels were used to define CIA. Results: We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 27 publications
(17 reference statements)
5
44
2
Order By: Relevance
“…A slightly higher level of creatinine could be attributed to several confounding factors, such as measurement reliability and patients' hydration, exercise level, or catabolism. It is difficult to explain the differences in relation to studies by Moon and others 16 and Mizuno and others, 17 in which the reported rates were much lower. Several factors could affect these results: differences in study populations, comorbidities, types of cancers, types of protocols, and the moment when serum creatinine was analyzed.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A slightly higher level of creatinine could be attributed to several confounding factors, such as measurement reliability and patients' hydration, exercise level, or catabolism. It is difficult to explain the differences in relation to studies by Moon and others 16 and Mizuno and others, 17 in which the reported rates were much lower. Several factors could affect these results: differences in study populations, comorbidities, types of cancers, types of protocols, and the moment when serum creatinine was analyzed.…”
Section: Discussionmentioning
confidence: 65%
“…Máthé and others 12 observed more severe nephrotoxicity in patients with hypertension associated with ischemic heart disease (20.9%) and those with diabetes mellitus associated with ischemic heart disease (30.8%), relative to patients without these comorbidities (7.5%). Mizuno and others 17 also observed an association between diabetes, heart disease, and stage 4 cancer and severe nephrotoxicity (defined as twice the baseline value).…”
Section: Discussionmentioning
confidence: 88%
“…25) In this study, heart disorders and hypoalbuminemia were risk factors for CIN, similar to recent findings. 24) Thus we clarified the threshold of the Alb value quantitatively. Multivariate logistic regression analysis suggested that cardiac disease and baseline Alb were significant risk factors.…”
Section: Discussionmentioning
confidence: 87%
“…The main risk factors for CIN such as older age, female gender, smoking, hypoalbuminemia, diabetes mellitus, and cardiovascular disease have been extensively studied. 10,17,24) However, these risk factors are not considered when making clinical decisions about treatment continua- 14) Differences in continuous data were compared using the Mann-Whitney U-test. * Significance level was set at p<0.05. tion, because they are non-numerical objective phenomena and cannot be used for treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] After administration of cisplatin, about 34% of patients develop renal dysfunction followed by acute kidney injury, which is associated with high morbidity and mortality. 3,8 The mechanism underlying cisplatin-induced nephrotoxicity is complex and not fully clear. The renal dysfunction is involved in mitochondrial oxidative stress, inflammation, and tubular necrosis.…”
Section: Introductionmentioning
confidence: 99%